Effects of Vitamin D Serum Level on Morbidity and Mortality in Patients with COVID-19: A Systematic Review and Meta-Analysis - Yiyun Hu; Janice Kung; Andrew Cave; Hoan Linh Banh (Frontiers Media S.A., 2022)
Purpose: It has been shown that low Vitamin D serum concentration is associated with increased pneumonia and viral respiratory infections. Vitamin D is readily available, inexpensive, and easy to administer to subjects infected with COVID-19. If effective in reducing the severity of COVID-19, it could be an important and feasible therapeutic intervention. Methods: We performed a systematic review and meta-analysis of the literature to determine the effects of Vitamin D serum concentration on mortality and morbidity in COVID-19 patients. The primary objectives were to determine if Vitamin D serum concentration decrease mortality, ICU admissions, ventilator support, and length of hospital stay in COVID-19 patients. Results: A total of 3572 publications were identified. Ultimately, 20 studies are included. A total of 12,806 patients aged between 42 to 81 years old were analyzed. The pooled estimated RR for mortality, ICU admission, ventilator support and length of hospital stay were 1.49 (95% CI: 1.34, 1.65), 0.87 (95% CI: 0.67, 1.14), 1.29 (95% CI: 0.79, 1.84), and 0.84 (95% CI -0.45, 2.13). Conclusion: There is no statistical difference in mortality, ICU admission rate, ventilator support requirement, and length of hospital stay in COVID-19 patients with low and high Vitamin D serum concentration.